A Survey on Capital Structure Decision of Nepalese Non-Financial Firm - Dhodary, Shanker (Pravaha, 2018)
The study aims at examining the views of capital structure in Nepalese non-financial enterprises. The study is based on primary data. A descriptive research design has been adopted for the study. Different descriptive statistical measures such as minimum, maximum, percentage, average, standard deviation and coefficient of variation have been used to analyze. This study is directed towards examining the capital structure policy of Nepalese non- financial firms. The primary information required for the said purpose has been collected through the survey of opinions of board of directors, company secretary, executives, chief finance officers and other line managers through administering the well structure multi- part questionnaire. For the purpose of field survey, 90 questionnaires were distributed among the respondents located in Kathmandu using non probabilistic sampling. The survey result shows that preference toward maturity structure of borrowing varied among the Nepalese non-financial firms, and majority of Nepalese firms do not consider interest rate and practice of matching between asset and liabilities structure while they go for borrowing. As proper matching between assets and liabilities structure is required, companies should pay attention towards this aspect. Outside security analysts and comparative industry have only a minimal effect on the development of these targets. Pravaha Vol. 24, No. 1, 2018, Page: 196-205